2022
DOI: 10.1111/cen.14826
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine complications after hematopoietic stem cell transplantation during childhood—Results from a close follow‐up in a cohort of 152 patients

Abstract: Context: Haematopoietic stem cell transplantation (HSCT) is a therapeutic option for numerous haematologic diseases and solid tumours. Increasing indications for HSCT and reduction in associated mortality have been raising the number of paediatric HSCT survivors and their long-term toxicities. Objective: To characterize the endocrine disorders developed after HSCT. Design and Patients: Retrospective analysis of 152 patients submitted to HSCT in paediatric age with at least 24 months of follow-up at our endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Another retrospective study from Spain involving 157 children post-HSCT presented similar risk factors for endocrinopathies including older age at HSCT, pubertal Tanner stage V, chronic graft-vs-host disease, direct gonadal therapy and specific treatments such as radiotherapy and steroids [ 15 ]. Figueiredo et al [ 16 ] also reported similar results from a study of 152 Portuguese patients after HSCT during childhood. We need to plan customized surveillance strategies based on the characteristics of the childhood cancer survivors.…”
supporting
confidence: 57%
“…Another retrospective study from Spain involving 157 children post-HSCT presented similar risk factors for endocrinopathies including older age at HSCT, pubertal Tanner stage V, chronic graft-vs-host disease, direct gonadal therapy and specific treatments such as radiotherapy and steroids [ 15 ]. Figueiredo et al [ 16 ] also reported similar results from a study of 152 Portuguese patients after HSCT during childhood. We need to plan customized surveillance strategies based on the characteristics of the childhood cancer survivors.…”
supporting
confidence: 57%
“…The incidence in our cohorts 2 and 3 fairly corresponds to a previous study on 109 patients aged 2-19 with malignant diseases who received TBI 12Gy/6 fractions between 1996 and 2015, of whom 12% developed GH deficiency and 12.5% hypothyroidism at median 8 (range 0.2-19) years follow-up (29). Another long-term follow-up including 152 HSCT recipients with both malignant and non-malignant diagnoses of whom 16% received TBI, reported a prevalence of both hypothyroidism and GH deficiency of 23% at median 9.9 years (30), where TBI was an independent risk factor for hypothyroidism, whereas craniospinal radiotherapy, but not TBI was associated with GH deficiency in the multivariate analysis (30). Disturbingly, in a cohort of patients younger than 3 years who received pre-HSCT conditioning with TBI 12Gy/6 fractions, 91.7% (11/12) developed GH deficiency and 35.7% (5/14) hypothyroidism by 1.8-13 years of follow-up (6).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Growth disorder is one of the most common late effects of allo-HSCT in children and often influences the final adult height among CCS. 13,14 Growth disorder in patients who have received allo-HSCT is caused by the growth hormone (GH) deficiency, which is induced by the irradiation to the pituitary-hypothalamus system. 15 The irradiation to the body is also associated with impaired bone growth.…”
Section: Introductionmentioning
confidence: 99%
“…The irradiation as a conditioning regimen or systemic steroids for the treatment of graft‐versus host disease (GVHD) directly inhibit the bone growth 17 . Previous reports revealed that growth disorder was associated with disease type, age at allo‐HSCT, and total dose of irradiation, and GVHD 13–18 . Therefore, there was a need for the establishment of the optimal strategy for allo‐HSCT to reduce the endocrine complications and improve the QOL of CCS who have received allo‐HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation